The Significance Of Social Media In The Insurance Industry In The Present Scenario (Trinity Journal of Management, IT & Media (TJMITM), 2016)
There is emergence of a number of major technology trends  impacting the insurance industry, one of these is the rise of  social media as a formidable socio cultural force, the implication  whereof will be instantaneous.Over the last one decade, social  media has been used by people for a number of motives:  entertainment, communicating, collaborating, seeking expert  advice, sharing information, sharing opinions, etc. Of late, social  scientists have observed that social media have increased people’s  connectivity and facilitated users’ direct involvement to a great  extent.This paper suggests that Social media can be best used by  the Insurance Industry for not only reducing operating cost but  also incurred claim ratio. To conduct this study, researcher has  extracted secondary data from various national and international  journals, reports, newspapers articles and websites.
Keywords: Social Media; social networking; social platforms; collaboration; insurance; claim processes